Awareness in Oral Hygiene Status in Diabetic Cases: An Institutional Study - Sreepreeti Champatyray1 , Saurjya Ranjan Das2 , Ipsita Mohanty3 , Neeta Mohanty4 , Jagannath Patro5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objectives: The objectives of the study were to: (1) assess the knowledge and awareness of diabetic patientsof their risk for systemic and oral diseases as complications associated with diabetes, (2) to assess theirattitudes toward sustaining good oral health through proper oral hygiene and regular dental check-ups, and(3) to the extent that they are aware, to determine how they became aware.Method: One hundred self-administered questionnaires were distributed to assess the main objectives of thestudy. Only completed questionnaires were used in the current study data analysis.Results: A majority of the participants suffering from Type 2 diabetes (58%). The awareness of diabeticpatients of their increased risk for oral diseases was not upto the benchmark point . Their attitude towardsgood oral hygiene status was not desired. Likewise, 43% brushed their teeth once daily and 49% never useddental floss. Regarding participants’ sources of awareness towards to dentist about diabetics is 50%.Conclusions: Diabetic patients are found to have little knowledge of their increased risk for oral diseases.Inorder to promote proper oral health and to reduce the risk of oral diseases, health professionals in boththedental and medical fields need to take the responsibility to develop programs to educate the public abouttheoral manifestations of diabetes and its complications on oral health.